Cancers that threaten women - Films for the Humanities and Sciences (New Jersey : Films for the Humanities and Sciences, 1991)
Ovarian and breast cancer are the principal focus of this program, which covers the symptoms, diagnosis, and treatment for ovarian cancer; guidelines for mammograms, and the need for early detection of breast cancer; the link between oral contraceptives and breast cancer, where there is an arguable increase, and endometrial and ovarian cancer, where there appears to be a decrease
Title from title screen
DVD format
Keywords: Cancer -- Patients; Breast -- Cancer; Ovaries -- Cancer; Women -- Health and hygiene; Women -- Diseases; Oral contraceptives -- Side effects